Fabrication of photoelectrochemical cell using highly compact vertical array zno nanorod - Taslim R.; Rahman M.Y.A.; Umar A.A.; Salleh M.M. (2023)
Highly compact vertical array ZnO nanorods on the FTO coated glass was fabricated for photoelectrochemical cell of FTO/ZnO/electrolyte/platinum. ZnO nanorods were grown on the FTO substrate at room temperature via ammonia assisted rapid hydrolysis process technique. In typical process, ZnO nanorods were characterized by FESEM with vertical array oriented with average diameter and length of 48 nm and 218 nm, respectively. The sample was grown throughout the surface by using four cycle growth process. The photoelectrochemical cell property was studied in dark and under illumination of 100 mWcm-2 light. The cell exhibits photovoltaic effect with JSC of 0.22mAcm-2, VOC of 0.44 V, and conversion efficiency of 0.03%.